Optimization of Polyamide Pulp-Reinforced Silica Aerogel Composites for Thermal Protection Systems - Ghica, Mariana E. (2020)
The present work describes for the first time the preparation of silica-based aerogel composites containing tetraethoxysilane (TEOS) and vinyltrimethoxysilane (VTMS) reinforced with Kevlar® pulp. The developed system was extensively investigated, regarding its physical, morphological, thermal and mechanical features. The obtained bulk density values were satisfactory, down to 208 kg·m-3, and very good thermal properties were achieved-namely a thermal conductivity as low as 26 mW·m-1·K-1 (Hot Disk®) and thermal stability up to 550 °C. The introduction of VTMS offers a better dispersion of the polyamide fibers, as well as a higher hydrophobicity and thermal stability of the composites. The aerogels were also able to withstand five compression-decompression cycles without significant change of their size or microstructure. A design of experiment (DOE) was performed to assess the influence of different synthesis parameters, including silica co-precursors ratio, pulp amount and the solvent/Si molar ratio on the nanocomposite properties. The data obtained from the DOE allowed us to understand the significance of each parameter, offering reliable guidelines for the adjustment of the experimental procedure in order to achieve the optimum properties of the studied aerogel composites.